Antibacterial and sporicidal activity of Eugenia polyantha Wight against Bacillus cereus and Bacillus subtilis - Lau, Kah Yan; Mohd Zainin, Nurul Syazwani; Abas, Faridah; Rukayadi, Yaya (Excellent Publishers, 2014)
The spore-forming bacteria, Bacillus spp., have often been associated with the contamination of rice and other starchy products. In this study, the extract of Indonesian bay leaf (Eugenia polyantha) was assessed for its antibacterial and sporicidal activities against vegetative cells and spores of Bacillus cereus ATCC33019 as well as Bacillus subtilis ATCC6633. The Minimum Inhibitory Concentration of E. polyantha extract against vegetative cells of B. cereus and B. subtilis were 0.31 and 0.63 mg/mL, respectively, while both their Minimum Bactericidal Concentration were 2.50 mg/mL. Time kill curves demonstrated that the bactericidal endpoint for B. cereus and B. subtilis was reached at concentration of 2.50 and 5.00 mg/mL, respectively (8× MIC) after 4 h of incubation. E. polyantha extract inactivated more than 3-log (99.99%) of B. cereus and B. subtilis spores at a concentration of 10.00 mg/mL (1.0%) after 1 h of incubation and the spores was completely killed at 25.00 mg/mL (2.5%). The sporicidal activity of E. polyantha extract was not affected by different temperatures treatment and alteration of pH. In conclusion, the potential anti-Bacillus activities of E. polyantha extract might support its use as a natural food preservative.